Chemical Resistance of Plastics and Elastomers : Rubbers, Thermoplastics, Thermoplastic Elastomers, and Thermosets. - Woishnis, William (Plastics Design Library [Imprint], William Andrew, Inc. Elsevier Science & Technology Books [distributor], 2007)
Annotation Chemical Resistance of Plastics and Elastomers is the world's largest compilation of data that explains the effect of thousands of reagents, the environment and other exposure media on the properties and characteristics of plastics and elastomers. Now with over 194,000 records, this fourth edition database is the most powerful tool any plastics engineer, researcher, or technician can use. Virtually everything you need to know about Chemical Resistance is right here. The Chemical Resistance database is truly comprehensive, providing as much information as is available from various sources which include technical journals, materials suppliers literature, electronic books, reference books, government publications, patents, test laboratories, and monographs. Incorporating and normalizing disparate data into an easy to use package is the hallmark of the Chemical Resistance brand. Hard to find information has been normalized to quickly provide answers to your questions and the highly regarded PDL rating is included for quick answers as to whether the material is suitable for further research. Extensive data is given for exposure conditions as well as the results of exposure. The interface allows you to basic search via keyword; advanced search using three distinct Boolean operators; or browse via material or reagent.
Keywords: Thermoplastics.; Elastomers.; elektronické knihy; electronic books